Was Vietnam's Economic Growth in the 1990s Pro-poor? An Analysis of Panel Data from Vietnam - Glewwe, Paul; Dang, Hai-Anh Hoang (2012)
International aid agencies and almost all economists agree that economic growth is necessary for reducing poverty, yet some economists question whether it is sufficient for poverty reduction. Vietnam enjoyed rapid economic growth in the 1990s, but a modest increase in inequality during that decade raises the possibility that the poor in Vietnam benefited little from that growth. This article examines the extent to which Vietnam's economic growth has been "pro-poor," giving particular attention to two issues. The first is the appropriate comparison group. When comparing the poorest x% of the population at two points in time, should the poorest x% in the first time period be compared to the poorest x% in the second time period (some of whom were not the poorest x% in the first time period) or to the same people in the second time period (some of whom are no longer among the poorest x%)? The second is measurement error. Estimates of growth among the poorest x% of the population are likely to be biased if income or expenditure is measured with error. Household survey data show that Vietnam's growth has been relatively equally shared across poor and nonpoor groups. Indeed, comparisons of the same people over time indicate that per capita expenditures of the poor increased much more rapidly than those of the nonpoor, although failure to correct for measurement error exaggerates this result.